Mixed gynecomastia - Qassabi, Salim S. Al (Saudi Med J, 2015)
Gynecomastia is an enlargement of male breast resulting from a proliferation of its glandular component, and it is usually due to an altered estrogen-androgen balance. It should be differentiated from pseudogynecomastia, which is characterized by fat deposition without glandular proliferation and from breast carcinoma. Gynecomastia could be physiological in neonates and pubertal or pathological due to drug intake, chronic liver, or renal disease, hyperthyroidism, testicular or adrenal neoplasms, and hypogonadism whether primary, or secondary. Properly organized work-up is needed to reach the cause of gynecomastia. Here, we reported a case of a young Omani man with gynecomastia with the aim of creating awareness of the occurrence of Klinefelter’s syndrome (KS) in patients with gynecomastia, to observe any differences in clinical presentation of KS from those reported in the literature, and highlight the needed diagnostic work-up and treatment.